Improving service quality. The case of United Insurance Company - Nguyễn, Chiến Thắng (Đại học Quốc gia Hà Nội, 2016)
From its inception and development, insurance has been recognized as having contributed significantly to ensure the continuity, stability and efficiency of the production, circulation and social consumption through financial supporting by claim activity. It also plays an important role in the development of financial markets through capital investment. There are several factors contributed to success of company including effectively utilizing resources, applying new modern technology to improve service quality and reducing price… On Vietnamese insurance market, insurers are mainly competing by reducing premium or increasing commission but they lack of service quality improving strategy. However, due to rapid development of market competition, those advantages are no longer reliable decisive factor in competition. Therefore, service quality is becoming more and more important for client to select and use a service. In the same market trend, United Insurance Company (UIC) has considered improving insurance service quality as the priority task of company.